Identification of Insect Pests on Rice Plants in Umbu Wangu Village for the Development of an Entomology E-Atlas - Talu, Martina Riani Dappa; Hildegradis Missa; Ndukang , Sardina; Djalo , Aloysius (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
Insects represent one of the most diverse groups of organisms, and many species act as destructive pests in rice ecosystems. However, the diversity of insect pests in Umbu Wangu Village has not been documented despite recurring yield losses reported by farmers. This study aimed to identify the insect pests associated with rice plants and to develop an electronic atlas (e-atlas) as a digital learning medium for the Entomology course. The research followed a Research and Development design using the ADDIE model, with field surveys carried out in rice fields of Umbu Wangu Village. Insect specimens were collected through direct capture and subsequently identified based on morphological characteristics. The results recorded seven pest species belonging to three orders: Hemiptera, Lepidoptera, and Orthoptera. To complement these findings, an e-atlas was designed as an instructional tool. Expert validation of the e-atlas yielded an average score of 85.5%, which falls into the “very valid” category, indicating strong feasibility for educational use. The documentation of pest diversity provides essential baseline data for local rice protection strategies. At the same time, the validated e-atlas offers an innovative medium that supports student-centered learning in entomology and bridges research outcomes with educational practice.